Technological potential of native lactic acid bacteria isolated from Swiss-type artisanal cheese (Ancash, Peru) for their application in food - Valdiviezo-Marcelo, Jaime; Arana-Torres, Nancy Maribel; Vega-Portalatino, Edwin Jorge; Ruiz-Flores, Luis Alberto; Tamariz-Angeles, Carmen; Olivera-Gonzales, Percy; Rosales-Cuentas, Miriam Marleni; Espinoza-Espinoza, Luis Alfredo (Frontiers in Sustainable Food Systems, 2023)
Swiss-type artisanal cheese is highly appreciated sensorially, its flavor is often associated with the lactic acid bacteria involved in its production, which in many cases are indigenous. Three artisanal Swiss-type cheeses of greatest preference in the market of Huaraz (Ancash) were selected. The main LAB were isolated and identified and their safety properties and technological potential for their application in new cheeses were verified in vitro and evaluated by consumers. Eleven strains were confirmed as LAB by Gram-positive and catalase-negative biochemical tests; according to 16S rDNA, seven strains belonged to Lacticaseibacillus paracasei (KQ3, EQ1, CQ1, YQ1, LQ2, GQ2 and TQ1), three strains to Lentilactobacillus parabuchneri (BQ2, OQ2 and RQ3), and one to Lactiplantibacillus sp. (QQ3). In safety assays, LAB did not exhibit gelatinase or hemolytic activities. In addition, L. paracasei KQ3, GQ2 and L. parabuchneri BQ2 effectively inhibited pathogens such as S. aureus, E. coli and L. monocytogenes. Antibiotic susceptibility was variable among strains. L. paracasei CQ1, EQ1, KQ3, TQ1 and Lactiplantibacillus sp. QQ3 showed high milk acidification capacity (0.16-1.44%) and reduced pH from 6.6 to 3.5 after 72 h of incubation. L. paracasei CQ1, Lactiplantibacillus sp. QQ3 and L. paracasei KQ3 showed the highest casein degradation zones (20.8-11.5 mm). All strains showed lipolytic activity, with Lactiplantibacillus sp. QQ3, L. paracasei CQ1 and L. parabuchneri BQ2 standing out with halos of 30.8-36.3 mm. Lactiplantibacillus sp. QQ3 and L. paracasei TQ1 showed ability to produce diacetyl. The best strains were tested in cheese production where L. paracasei CQ1 showed the best sensory qualities. Finally, the native BAL strains showed a high potential for the production of natural, safe and sensorially acceptable dairy products.